Implementasi User Centered Design Untuk Sistem Pengajuan Surat Pada Kelurahan Mentawa Baru Hulu Sampit - Muhammad Fajrin Anshari; Depi Rusda (LPPM UBHINUS MALANG, 2022)
The rapid development of information technology in the modern era makes information technology very helpful in simplifying and accelerating work. A website-based information system is one of the options to be applied in the process of submitting a resident letter in the Kelurahan Mentawa Baru Sampit because the process of using it can make it easier for agencies, as well as the community and the community, do not need to visit the village directly. The information system can also minimize crowds, and prevent the transmission of Coronavirus Identified-19 (Covid-19) which is a world pandemic. The use of the User Centered Design method can find a solution to the needs desired by the user, then the solution offered is financially feasible to design the design that the user wants so that it can be implemented. This study discusses the initial to the final stages of the UCD method. The testing or evaluation is done by testing the Black Box and using the System Usability Scale (SUS) questionnaire. Tests carried out using the black box, the system has functioned well while using SUS the Acceptable Ranges level is in the Acceptable range, the Grade Scale is in the B range, and the Adjective Rating is in the Excellent range.